MATHEMATICS TEACHER’S PERCEPTIONS ABOUT INFLUENCE OF DIFFERENT ICT USAGE STRATEGIES ON THEIR COMPETENCIES - Ljajko, Eugen (Bulletin of Natural Sciences Research, 2020)
Teacher competencies are among the key factors of a successful mathematics instruction. The main goal of the study was to compare teachers’ beliefs and attitudes affected by different strategies in organizing the instruction process. The study gives a comparison of teachers’ competencies in three groups of teachers – one teaching mathematics without ICT, the second using ready-made GeoGebra applets and the third one developing their own GeoGebra applets in cooperation with their students. The survey includes 65 mathematics teachers working in 21 primary and secondary schools in southern regions of Serbia. We observed, assessed and compared affective-motivational characteristics of teachers – their beliefs and professional motivation. Results indicate that the teachers’ affective-motivational characteristics depend on the way they employ technology in representing the content they teach. If the technology is used in an inappropriate manner it can impede the students’ creativity, but it also obstructs teachers in deploying their full abilities in the process. The results also bring to the fore issues concerning ways to maintain positive effects achieved through ICT empowered instruction organized in the way the third group of teachers did.